Teledermatology for managing COVID-19 patients with cutaneous manifestation: case series study in a rural primary hospital - Dedianto Hidajat; Hamsu Kadriyan; Slamet Tjahjono (Intisari Sains Medis, 2022)
Background: To provide information and experience about using WhatsApp as a tool in teledermatology to facilitate the identification, treatment, and follow-up of skin problems in COVID-19 patients hospitalized at one of a rural primary hospital located in Indonesia.Methods: All COVID-19 patients with the dermatology manifestation were included in this study. All symptoms and signs of cutaneous manifestation and teledermatology consultation aspect were recorded.Results: There were 7 cases confirmed with skin manifestation (0.9%) from 783 hospitalized patients from March 2020 to June 2021. There were 5 males and 2 females. The age range was 50 - 66 years old. Pruritus is the main complaint, followed by pain and swelling. The cutaneous lesions were mainly maculopapular, followed by papulovesicular and edematous eruptions. The onset of the lesions appeared between the 2nd and 12th day during hospitalization. Both patients and physicians feel comfortable using this platform in consultation.Conclusion: There are advantages and disadvantages to utilizing this concept in the medicolegal aspects, including non-uniform audio-visual quality and also ethical and privacy issues, especially in a rural area.